1988
DOI: 10.3109/00016488809107375
|View full text |Cite
|
Sign up to set email alerts
|

The bayesian approach to the evaluation of risk factors in acute and recurrent acute otitis media

Abstract: A multivariant modelling method was used to analyse the risk, associated with 22 different factors, of contracting acute otitis media (AOM) in a prospective cohort of 1294 urban children followed up to the age of 17-32 (mean 25) months. By far the most important risk factor was the caring of the child at a day-care centre. The importance of this factor further increased with increasing recurrence of the attacks. Next in order came the existence of sibling(s) with AOM attacks during the follow-up. Prolongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 13 publications
3
40
0
1
Order By: Relevance
“…22 Socioeconomic deprivation has been described as a risk factor for acute and recurrent OM associated in numerous international studies. [32][33][34] Determining the basis for disparate prevalence and treatment of OM in children from lower socioeconomic strata is essential to identify barriers that prohibit these children from accessing timely and appropriate evaluation and therapy for OM.…”
Section: Discussionmentioning
confidence: 99%
“…22 Socioeconomic deprivation has been described as a risk factor for acute and recurrent OM associated in numerous international studies. [32][33][34] Determining the basis for disparate prevalence and treatment of OM in children from lower socioeconomic strata is essential to identify barriers that prohibit these children from accessing timely and appropriate evaluation and therapy for OM.…”
Section: Discussionmentioning
confidence: 99%
“…1 These conditions are often treated with tympanostomy tubes to ventilate the middle ear; this is the most common surgical procedure performed in children in an ambulatory setting. 8 Epidemiologic studies 2,9,10 have shown that a family history of these conditions increase a child's personal risk for COME/ ROM, and twin studies 11,12 have demonstrated a high degree of heritability for ROM and otitis media (OM) duration. We conducted a linkage study (the Minnesota COME/ROM Family Study 13 ) that revealed evidence for linkage to COME and ROM on chromosome 10q and suggestive evidence for linkage on chromosome 19q.…”
mentioning
confidence: 99%
“…Therefore, if household smoking is associated with the risk of middle ear disease, there should also be a relationship between socio-economic factors and these diseases. However, only 6 of the studies [24,28,34,45,47,48] found an association between socio-economic status and the incidence of middle ear diseases, although raised relative risks were found for various other factors which may be indicative of lower social class.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke may also have an indirect effect via the child's respiratory system, either through a reduction in immune response resulting in more frequent respiratory illnesses [2,17,19,68,69,73,76,82,94,98], or through cross-infection from adult smokers who may themselves suffer an increased frequency of respiratory infections [17,19,47,70,73,101,102]. It has been suggested that this second pathway may be a more important cause of respiratory illnesses than a direct effect of tobacco smoke on the child's own respiratory system [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation